Analysis of PT. Siantar Top, Tbk Financial Statements for The Period 2021-2023 as an Effort To Measure Company Financial Performance - Solehatun Munawaroh; Khariratun Horisah (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Increasingly fierce competition in the snack food industry is driving companies to continuously improve their financial performance. One important indicator in evaluating a company's performance is the financial statement, which contains information about the company's financial position, operational performance, and changes in financial condition. This research aims to assess the financial performance development of PT. Siantar Top, Tbk during the period from 2021 to 2023, focusing on profit growth and the analysis of four types of financial ratios: liquidity, solvency, activity, and profitability ratios. The method used in this study is qualitative descriptive analysis using secondary data obtained from the company's financial statements over the past three years. The research results indicate that PT Siantar Top demonstrates excellent financial performance with sustainable growth in assets, equity, and profits. Prudent liquidity and debt management, combined with improved profitability, position the company well to face industry challenges and compete with other players in the snack food sector.